LATIHAN YOGA SURYANAMASKAR UNTUK MENINGKATKAN KONSENTRASI BELAJAR : KAJIAN LITERATUR - Ismail, Suhartini; Tri Vita Amalia (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2021)
Concentration is the focus of one's mental and physical energies on a task at hand, dismissing or putting aside all thoughts and actions that are unrelated to the task at hand. Low learning concentration is a problem that most students suffer, according to various research findings. This literature review aims to determine the influence of Suryanamaskar practicing yoga on learning concentration. The effect of yoga Suryanamaskar on learning concentration was researched and published in using databases of Sciencedirect, PubMed, Proquest, and Google Scholar, with the following inclusion criteria: published between 2010 to 2020 and English articles The keywords of searching used Yoga Suryanamaskar, college students, and learning concentration. Ten studies found that the yoga Suryanamaskar improves learning concentration by increasing features such as concentration, attention, relaxation, cognitive function, and memory. Suryanamaskar yoga has a favorable influence on learning concentration, according to the findings. As a result, a nursing school might teach Suryanamskar yoga on a regular basis to help nursing students focus on their studies.